A toolkit of thread-based microfluidics, sensors, and electronics for 3D tissue embedding for medical diagnostics. - Sonkusale, Sameer.; Mostafalu, Pooria.; Akbari, Mohsen.; Alberti, Kyle A.; Xu, Qiaobing.; Khademhosseini, Ali. (Tufts University. Tisch Library., 2016)
Threads, traditionally used in the apparel industry, have recently emerged as a promising material for the creation of tissue constructs and biomedical implants for organ replacement and repair. The wicking property and flexibility of threads also make them promising candidates for the creation of three-dimensional (3D) microfluidic circuits. In this paper, we report on thread-based microfluidic networks that interface intimately with biological tissues in three dimensions. We have also developed a suite of physical and chemical sensors integrated with microfluidic networks to monitor physiochemical tissue properties, all made from thread, for direct integration with tissues toward the realization of a thread-based diagnostic device (TDD) platform. The physical and chemical sensors are fabricated from nanomaterial-infused conductive threads and are connected to electronic circuitry using thread-based flexible interconnects for readout, signal conditioning, and wireless transmission. To demonstrate the suite of integrated sensors, we utilized TDD platforms to measure strain, as well as gastric and subcutaneous pH in vitro and in vivo.